MAKNA METAFORA ANJING MENJULURKAN LIDAH DALAM SURAH AL-A’RAF AYAT 176: Pendekatan Psikologi Eksistensial - Amiyati Amiyati; Valisa Valisa; Paudji Astuti; Ahmad Mujahid (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The parable of the dog in Surah Al-A'raf verse 176 is a rich symbolization of the psychological state of human beings who experience dissatisfaction with life. This study seeks to uncover the layers of existential meaning of the metaphor through thematic approach and existential psychology. Using a qualitative-interdisciplinary methodology, this study combines thematic interpretation analysis (maudhu’i) with theory, especially the thought of Viktor Frankl and Carl Gustav Jung. The results show that the dog's behavior of "sticking out its tongue," both when it is expelled and when it is left alone, reflects the human soul, which is always restless, thirsty for meaning, and never feels enough, even when it has gained knowledge and guidance. This phenomenon is consistent with the symptoms of existential emptiness, anxiety, and value disorientation experienced by many modern people, especially in the post-pandemic era. The implications of this study underscore the importance of strengthening spiritual values as a foundation for facing life's challenges and prove the relevance of the Qur'an as a source of solutions to mental problems and the search for the meaning of life in the modern age.